2002
DOI: 10.1074/jbc.m204885200
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Synergistic Effect of Muramyl Dipeptide with Endotoxin and Peptidoglycan

Abstract: Although the basis for the high mortality rate for patients with mixed bacterial infections is likely to be multifactorial, there is evidence for a synergistic effect of muramyldipeptide (MDP) with lipopolysaccharide (LPS) on the synthesis of proinflammatory cytokines by mononuclear phagocytes. In this study, co-incubation of human Mono Mac 6 cells with MDP and either LPS or peptidoglycan (PGN) resulted in an apparent synergistic effect on tumor necrosis factor-␣ (TNF-␣) secretion. Although incubation of cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
108
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 38 publications
17
108
0
2
Order By: Relevance
“…Indeed, the synergistic production of IL-1b by MDP and LPS is caspase-1dependent, and not regulated at transcriptional level. However, in line with other studies, we show that the mechanism of synergy for TNF-a is exerted at a transcriptional level [40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, the synergistic production of IL-1b by MDP and LPS is caspase-1dependent, and not regulated at transcriptional level. However, in line with other studies, we show that the mechanism of synergy for TNF-a is exerted at a transcriptional level [40].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the synergistic production of IL-1b by MDP and LPS is caspase-1dependent, and not regulated at transcriptional level. However, in line with other studies, we show that the mechanism of synergy for TNF-a is exerted at a transcriptional level [40].In conclusion, we demonstrate that NOD2 is nonredundant for both the production of IL-1b mRNA and the IL-1b release from the activated cells. In addition, indirect data supports a role for NOD2 in the activation of caspase-1 in human MNC after stimulation with MDP.…”
supporting
confidence: 92%
“…The following observations could account for the actual TLR/Nod synergy: (i) LPS stimulation upregulates Rip2 expression in murine macrophages, 80 (ii) TAK1, a molecule implicated in the canonical MyD88-dependent TLR signaling, has also been shown to participate in the Nod2 pathway, 93 (iii) MDP stimulation upregulates MyD88 expression, 133 (iv) MDP-stimulated macrophages induce a significant upregulation of TNF mRNA, and LPS costimulation efficiently enhances TNF mRNA translation and release. 134 It is possible that all the above observations contribute, in part, to the synergistic effect of Nods on TLR signaling, and that not a single mechanism is responsible for the global effect.…”
Section: Nods/tlrmentioning
confidence: 99%
“…[238][239][240][241][242] Nod1 and Nod2 activation also drive adaptive immune responses. Kobayashi et al have shown that Nod2 mediates adjuvant activity through the production of IgG1-type antibodies to T-cell-dependent antigens.…”
Section: Intracellular Tlr7 Activation: Imidazoquinoline Ligandsmentioning
confidence: 99%